Influência do cimento rico em pozolana e da emulsão asfáltica na porosidade e propriedades mecânicas da BGTC - Nunes, Verônica Janaína Melo Barreto (2022)
On roads with high traffic loads, cement-treated crushed stones (CTCS) bases and sub-bases are alternatives to increase the load capacity of the structure and reduce pavement deformations. However, these mixtures present a heterogeneous matrix and a high percentage of voids in their structural arrangement, even considering the modified compaction energy and the granulometric arrangement in the sense of designing the mixture with the concept of maximum densification. Thus, knowing the negative effects of the high percentage of voids in the CTCS, the present study aimed to analyze the influence of the use of asphaltic emulsion as an additive to the mixture and the type of Portland cement in the reduction of the porosity of the CTCS and in the improvement of its mechanical properties. For this, an experimental plan consisting of physical characterization tests, mechanical tests and porosity evaluation was elaborated. Adopting the mixtures with 3.0% and 5.0% of CP II-F 32 as reference mixtures in their respective cement contents, the mechanical properties of mixtures of BGTC with 3.0% and 5.0% of CP IV 32 RS were analyzed as well as the properties of mixtures with 3.0% CP II-F 32 using asphaltic emulsion as additive. The results obtained for the mixtures studied indicated that, of the evaluated parameters (cement content, type of cement, curing time and use of asphalt emulsion), as expected, the cement content in the mixtures presents greater significance in the increase of stiffness, resistance and CTCS porosity reduction. It was found that, for the same cement content, the replacement of CP II-F 32 cement by CP IV 32 RS cement in the cement mixtures is responsible for the increase in strength and stiffness, and for the reduction of porosity. With regard to the use of cationic asphaltic emulsion as an additive to CTCS, the slow rupture resulted in the reduction of RCS and RTCD after 7 days of curing, in all investigated contents. On the other hand, the use of 0.5% fast breaking asphalt emulsion was responsible for the increase in the tensile and compressive strength at 28 days and for the reduction in the porosity of the CTCS. It was verified, still, the relation between the porosity reduction and the better mechanical performance (resistance and rigidity) in the mixtures studied. The images of the macrostructure (high resolution images) and microstructure (by SEM) corroborate the results obtained in the laboratory, being possible to observe a more compact and dense structure in the mixtures that obtained lower void and absorption indices.